Дослідження конкурентоспроможності закладів вищої освіти: сутність та диференційований підхід до визначення - Косар, Н. С.; Кузьо, Н. Є.; Сулим, Т. А.; Kosar, N. S.; Kuzo, N. Ye.; Sulym, T. A. (Видавництво Львівської політехніки, 2020)
На підставі проведеного аналізу визначено сутність терміну “конкурентоспроможність закладу вищої освіти” на ринку та його головні ознаки. З використанням результатів опитування споживачів, аналізу нормативних документів, що регулюють освітню діяльність та іншої вторинної маркетингової інформації подано основні показники оцінки конкурентоспроможності закладу вищої освіти для споживачів освітніх послуг, системи вищої освіти та суспільства.

Basing on the conducted analysis, the authors determined the essence of the notion of “competitiveness of a higher education establishment” at the market, which is considered as a capacity to best satisfy the current and influence formation of the future needs of consumers by means of prices, quality of education services and supplied range of products at the specified market of educational services in the set period of time. Moreover, it is necessary to support the desired social focus and personal sustainable development of the education establishment due to its acquired competitive advantages. It is substantiated that the main characteristics of the category of “competitiveness of higher education establishments” include comparability, spatiality, dynamism, concreteness, attributiveness, consistency, objectiveness. Referring to the results of consumers’ interviewing, analysis of the regulatory documents on educational activities and other secondary marketing information, the authors identified the principal indices of assessment of competitiveness of higher education establishments, supplied for consumers of educational services, system of higher education and society. For higher education consumers, they include a group of indices characterizing the supplied educational services, accommodation and leisure activities for the students of different levels, information support for educational process, and its financial and logistical support. In terms of higher education, it concerns national and international ratings, relevance of the indices tothe supplied educational services, level of research activity at the higher education establishment, and staff qualification. The most important groups of indices for assessment of competitiveness of a higher education establishment in terms of its social importance include the education establishment image, number of students of different educational levels, and its social activity. The current work mentions the recommended components for each of the abovementioned groups of indices for assessment of competitiveness of a higher education establishment. It is proposed to calculate the integral index of competitiveness of a higher education establishment at the market with consideration of the values of partial indices of competitiveness, which are set for different entities of the educational services marketand the relevant weight factors.
Investigation of competitiveness of higher education establishments: , essence and differentiated approach to determination
Keywords: ринок освітніх послуг; заклад вищої освіти; конкурентоспроможність; споживачі освітніх послуг; інтегральний показник конкурентоспроможності закладу вищої освіти; market of educational services; higher education establishment; competitiveness; consumers of educational services; integral index of competitiveness of a higher education establishment; 378.1; 339.137